2020
DOI: 10.3390/app10051610
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Muscle Injuries in an Elite Spanish Male Academy Soccer Club: A Hamstring Injuries Approach

Abstract: The aims of this study were to analyze the muscle injury incidence in an elite Spanish soccer academy during three consecutive seasons attending to different chronological age groups (i.e., U14, U16, U19 and senior) and to examine the hamstring injury incidence in this elite soccer academy. Elite male youth soccer players (227) participated in this study. A total of 207 time-loss injuries (i.e., injuries that involve at least one absence day) were observed during this study period. The overall incidence rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
(96 reference statements)
6
26
1
2
Order By: Relevance
“…In men’s club football, the UEFA Elite Club Study (UECS) [ 10 ] has provided a commonality in definitions and the injury and illness reporting process [ 11 ], and has provided an insight into injury and illness in men’s professional football in the European leagues [ 10 , 12 ]. Epidemiological information also exists in elite youth football [ 13 , 14 ]. However, while these studies provide useful information, data from international or women’s football does not form part of their analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In men’s club football, the UEFA Elite Club Study (UECS) [ 10 ] has provided a commonality in definitions and the injury and illness reporting process [ 11 ], and has provided an insight into injury and illness in men’s professional football in the European leagues [ 10 , 12 ]. Epidemiological information also exists in elite youth football [ 13 , 14 ]. However, while these studies provide useful information, data from international or women’s football does not form part of their analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Attending to youth populations, Asai et al [31] showed a higher incidence in sprain injuries (128 injuries), with very high values compared to contusions (80 injuries). These differences with senior players could be due to youth players still not having a fully developed musculoskeletal system [54]. However, this finding should be taken with caution because of the lack of studies reporting injury type in youth handball players [31].…”
Section: Location and Type Of Injuriesmentioning
confidence: 89%
“…1,17 Furthermore, there has been an increased recognition that injury burden (e.g the number of absence days per 1000 h of exposure time) is an important parameter to report, especially in relation to specific positions within team sports. 2,29 Despite the fact that this valuable information could help to develop successful risk management strategies, burden has not been previously reported in professional handball players.…”
Section: Introductionmentioning
confidence: 99%